2005
DOI: 10.7748/ns.19.24.33.s54
|View full text |Cite
|
Sign up to set email alerts
|

Communication about sexual problems in male patients with multiple sclerosis

Abstract: Rehabilitation teams need training to deal with patients' sexual problems, and the nurse is likely to be identified as the specialist in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 0 publications
0
47
0
3
Order By: Relevance
“…Six articles were located from the database search [13–18] and two additional articles were identified from checking reference lists [19,20]. One other article was also identified through reference lists [21]; however, it was not included as it was clearly a duplication of another article included in the review (this was acknowledged by the authors).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six articles were located from the database search [13–18] and two additional articles were identified from checking reference lists [19,20]. One other article was also identified through reference lists [21]; however, it was not included as it was clearly a duplication of another article included in the review (this was acknowledged by the authors).…”
Section: Methodsmentioning
confidence: 99%
“…Eight articles were therefore included in the final review [13–20]. It was apparent that some articles reported on findings from the same study, which was evident from the authors, location, and sample size being the same (articles 14–17 reported on findings from the same study and articles 18 and 20 reported on findings from the same study).…”
Section: Methodsmentioning
confidence: 99%
“…Sexual communication skills are generally poor in the community (Roberts, 1992;Rubin, 2005) and amongst health professionals (Gott et al, 2004). This difficulty increases if illness, disability or aging are involved.…”
Section: Margaret Juliet Redelmanmentioning
confidence: 97%
“…Many sources in the nursing literature have used the PLISSIT model to illustrate an appropriate recognition of client needs and an approach for intervention [10]. Authors have described the use of the model with patients who had spinal cord injury, Hodgkin's disease, cancer and myocardial infarction [8][9][10][11][12][13]. However, in the literature, this model was found to be used only in one study of patients who had a stoma [14].…”
Section: Introductionmentioning
confidence: 98%
“…This model allows nurses in addressing sexual problems to start a discussion regarding sexual issues with individuals. In addition, this model can guide nurses in planning issues to be discussed with individuals, and useful information and suggestions to be incorporated to care plan [8,9]. Many sources in the nursing literature have used the PLISSIT model to illustrate an appropriate recognition of client needs and an approach for intervention [10].…”
Section: Introductionmentioning
confidence: 99%